Automatic multiple Kinect cameras setting for simple walking posture analysis - Kaenchan, Suttipong; Mongkolnam, Pornchai; Watanapa, Bunthit; Sathienpong, Sasipa (2013 International Computer Science and Engineering Conference (ICSEC), 2013)
We propose an automatic setting of multiple skeletal tracking Kinect cameras, in lieu of mere using a single camera, to capture a human skeleton because of possible viewing occlusions. Using multiple cameras from different angles gives a more complete whole body; however, more required steps are needed in combining multiple skeletons into one final skeleton. One camera is used as a reference for the other cameras to transform their coordinates into the reference camera's coordinate system. Once every view is in the same coordinate, one skeleton is able to be composed. Due to camera's sensory errors, nevertheless, the supposedly same joint of the skeleton, which is obtained from the transformations, may not be exactly located at the same position. Therefore, average joints are used for the composed skeleton. The skeleton is then used to analyze the walking posture of a human subject in order to check whether or not the walking is balanced.